The Nursing Activities Score and its association with healthcare-associated infections in a Brazilian adult intensive care unit (Research, Society and Development, 2022)
The intensive care unit (ICU) requires a specialized team with adequate human resources, including nursing. For an adequate measurement of the workload of nursing professionals of Brazilian ICUs, the Nursing Activities Score (NAS) has been used to promote better adequacy of work scales. Work overload can increase the incidence of adverse events, including healthcare-associated infections (HAI). Objective: To associate the nursing workload measured by the NAS with the rates of HAI in an Adult ICU of a university hospital, in addition to evaluating the impact of the separation of ICUs by unit, or type of specialization. Method: Data collection was performed at Brazil, in the Adult ICU: stratified by the Surgical, Neurological and Medical specialties; including the calculation of the means of NAS and the monthly rates of HAI of each ICU unit, from 2016 to April 2019. NAS data were collected from secondary spreadsheets, without identification of the patient, and the rates of HAIs were collected from information from the Hospital Infection Control Service. Results: The mean NAS was different for each unit, with Neurological unit with the highest mean. In relation to HAIs, neurological unit patients had a higher incidence of HAIs and patients with HAIs. Pneumonia associated with mechanical ventilation (VAP) was higher in Surgical and Neurological units. Bloodstream and urinary tract infection were higher in the Medical unit. There was a positive correlation for NAS and VAP in the Medical unit and with urinary tract infection in the Surgical unit. In the Neurological unit there was a negative correlation with the rate of HAI and rate of patients with HAI. Conclusion: The mean NAS observed by us was lower when compared to other ICUs and variations may be associated with the type of hospital and clinical profile of patients. It was possible to observe that each unit has its particularity regarding the incidence of HAIs and the association between NAS (nursing workload) and rates, reinforcing the need for stratification and association of indicators per unit.